Potential impact of ezetimibe on patients with NAFLD/NASH: a meta-analysis of randomized controlled trials - Jiao, BoLun; Wang, Bing; Liu, BoYan; Zhao, Jin; Zhang, YunHao (Frontiers in Endocrinology, 2024)
Background Non-alcoholic fatty liver disease (NAFLD) is now the most common cause of chronic liver disease. Studies have found that ezetimibe may be utilized as a supplemental treatment for NAFLD. Additionally, many clinical trials reported the potential impacts of ezetimibe on patients with NAFLD, although some conclusions remain controversial. Therefore, this study aimed to evaluate the effects of ezetimibe on patients with NAFLD. Method Online search was conducted across databases including PubMed, Embase, Scopus, Web of Science, Cochrane Library, Wanfang, VIP, and CNKI to retrieve all relevant controlled studies on the treatment of NAFLD with ezetimibe from the inception of the databases until April 2024. This meta-analysis comprised 10 randomized controlled trials (RCTs). Statistical analysis was conducted using the Meta package in R v4.3.2. Results A total of ten RCTs were included in this study, encompassing 578 patients (290 in the ezetimibe group and 288 in the control group) diagnosed with NAFLD/non-alcoholic steatohepatitis (NASH). The results indicated that ezetimibe significantly reduced levels of aspartate aminotransferase (P < 0.01), glutamyl transferase (γ-GT) (P < 0.01), total cholesterol (P < 0.01), low-density lipoprotein cholesterol (P < 0.01), high-sensitivity C-reactive protein (P < 0.01), and interleukin-6 (P < 0.01), and markedly increased levels of glycated hemoglobin (P = 0.02). Conclusions Ezetimibe may partially improve transaminase levels and positively impact liver function in patients with NAFLD/NASH. Systematic Review Registration https://www.crd.york.ac.uk/PROSPERO/, identifier CRD42023461467.